Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pone.0150545
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Quality of Life Based on the KIDSCREEN-27: Child Self-Report, Parent Ratings and Child-Parent Agreement in a Swedish Random Population Sample

Abstract: BackgroundThe KIDSCREEN-27 is a measure of child and adolescent quality of life (QoL), with excellent psychometric properties, available in child-report and parent-rating versions in 38 languages. This study provides child-reported and parent-rated norms for the KIDSCREEN-27 among Swedish 11–16 year-olds, as well as child-parent agreement. Sociodemographic correlates of self-reported wellbeing and parent-rated wellbeing were also measured.MethodsA random population sample consisting of 600 children aged 11–16,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
51
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 30 publications
10
51
2
7
Order By: Relevance
“…Also, in self‐report studies, the possibility of bias due to overreporting or underreporting cannot be excluded. Response shift bias can also influence the outcomes of such studies, as patients with chronic illnesses or disabilities may develop increased tolerance and acceptance of problems because of a change in standards, values and conceptualisations of themselves and their lives . The self‐reported HRQoL levels seen in our study may, therefore, not fully reflect the impact of the patients’ illness and treatment history on their HRQoL.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Also, in self‐report studies, the possibility of bias due to overreporting or underreporting cannot be excluded. Response shift bias can also influence the outcomes of such studies, as patients with chronic illnesses or disabilities may develop increased tolerance and acceptance of problems because of a change in standards, values and conceptualisations of themselves and their lives . The self‐reported HRQoL levels seen in our study may, therefore, not fully reflect the impact of the patients’ illness and treatment history on their HRQoL.…”
Section: Discussionmentioning
confidence: 89%
“…The patients in our study reported slightly higher HRQoL than the European norm values for patients aged 8–18, while the outcomes did not differ from the Swedish reference data for those aged 12–18. This observation may, to some extent, be attributed to the fact that the Swedish norm scores have been found to exceed those of the European norms in most of the KIDSCREEN‐52 subdimensions .…”
Section: Discussionmentioning
confidence: 99%
“…Da mesma forma, num estudo realizado na Suécia, em 2012, com 600 crianças e adolescentes com idades compreendidas entre 11-16 anos, a perceção de QVRS foi significativamente mais baixa em adolescentes do que em crianças. (17) A diminuição de bem-estar relacionada à idade pode estar associada com a transição física, cognitiva e social da infância para a vida adulta que os rapazes e meninas enfrentam neste estágio. Essas mudanças podem incluir: mudanças físicas, uma nova aparência física que provoca insatisfação e ansiedade; mudanças cognitivas, novas ferramentas cognitivas que permitem que os adolescentes tenham acesso a pensamentos mais complexos (sobre o mundo em geral e sobre si mesmos e suas circunstâncias particulares), a procura da sua própria identidade e mudanças sociais, novos desafios sociais associados a mudanças de relacionamento com pais e colegas, primeiros amores, primeiras experiências sexuais, entre outras.…”
Section: Discussionunclassified
“…No que diz respeito às pessoas com quem as crianças e adolescentes habitam, na maioria das dimensões não foram encontradas diferenças significativas, à exceção da dimensão Saúde e atividade física, Estado de humor geral e Questões económicas. O presente estudo mostra que as crianças e adolescentes que coabitam numa família nuclear apresentam melhor perceção sobre a própria QVRS, indo de encontro aos resultados do estudo realizado por Berman et al, (17) em que o autor verificou que as crianças e adolescentes que habitavam com ambos os pais apresentavam melhor perceção sobre a própria QVRS.…”
Section: Discussionunclassified
“…KIDSCREEN-52 self-reported version has earlier been used in Swedish studies , Svedberg, Eriksson et al 2013, Omma and Petersen 2015 as well as the shorter forms of the questionnaire, KIDSCREEN-27 and KIDSCREEN-10 , Jervaeus, Kottorp et al 2013, Jervaeus, Lampic et al 2014, Berman, Liu et al 2016). …”
Section: Questionnairesmentioning
confidence: 99%